The cuticle modulates ultraviolet reflectance of avian eggshells - Fecheyr-Lippens, Daphne C; Igic, Branislav; D'Alba, Liliana; Hanley, Daniel; Verdes, Aida; Holford, Mande; Waterhouse, Geoffrey I N; Grim, Tomas; Hauber, Mark E; Shawkey, Matthew D (Biology open, 2015)
Avian eggshells are variedly coloured, yet only two pigments, biliverdin and protoporphyrin IX, are known to contribute to the dramatic diversity of their colours. By contrast, the contributions of structural or other chemical components of the eggshell are poorly understood. For example, unpigmented eggshells, which appear white to the human eye, vary in their ultraviolet (UV) reflectance, which may be detectable by birds. We investigated the proximate mechanisms for the variation in UV-reflectance of unpigmented bird eggshells using spectrophotometry, electron microscopy, chemical analyses, and experimental manipulations. We specifically tested how UV-reflectance is affected by the eggshell cuticle, the outermost layer of most avian eggshells. The chemical dissolution of the outer eggshell layers, including the cuticle, increased UV-reflectance for only eggshells that contained a cuticle. Our findings demonstrate that the outer eggshell layers, including the cuticle, absorb UV-light, probably because they contain higher levels of organic components and other chemicals, such as calcium phosphates, compared to the predominantly calcite-based eggshell matrix. These data highlight the need to examine factors other than the known pigments in studies of avian eggshell colour.
Keywords: Light modulation; Biomimicry; Ultraviolet reflectance; Cuticle; Avian eggshells